THE HIGH ELEVATION OF C-REACTIVE PROTEIN LEVELS AT ADMISSION REPRESENTS AN EARLY MORTALITY PREDICTOR IN PATIENTS WITH COMPLICATED INTRA-ABDOMINAL INFECTIONS - E. Dimitrov; G. Minkov; E. Enchev; S. Nikolov; A. Petrov; Y. Yovtchev (Trakia Journal of Sciences)
PURPOSE: The aim of this study was to evaluate the highly elevated CRP levels at admission as a mortality predictor in patients with complicated intra-abdominal infections (cIAIs). METHODS: This retrospective study involved 78 adult patients with diagnosis cIAIs admitted to the Department of Surgical Diseases at a University Hospital Stara Zagora from January 2017 to October 2018. CRP concentrations, white blood cells (WBC) count, qSOFA score and SIRS criteria were determined at admission. We compared their prognostic performance using the area under receiver operating characteristics (AUROC) curves and analyzed the coordinates of the curves. RESULTS: Of the 78 enrolled patients twenty (25.6%) died during hospitalization. ROC Curve analysis revealed CRP as the best mortality predictor (AUROC = 0.787). The pairwise comparison of ROC curves showed prognostic superiority of CRP compared to WBC (AUROC = 0.787 vs. 0.511, p = 0.0194) and SIRS (AUROC = 0.787 vs. 0.579, p = 0.0315) in outcome prediction. The identified sensitivity and specificity for CRP cut-off value = 210 mg/L were 75.0% and 81.0%, respectively. CONCLUSION: We found highly elevated CRP levels at admission as a significant prognostic biomarker in patients with cIAIs.